SISTEM INVENTORY BERBASIS MULTIUSER DI TOKO BESI MINI SEMARANG - A. Rifky Purnama; Budi Hartono (STEKOM PRESS, 2018)
Semarang Mini Iron Shop has 5 employees and a leader. Mini Iron Stores Semarang do the buying and selling process wholesale with various customers, the majority of which are small traders or retailers. In running its business, Semarang Mini Iron Shop still conducts conventional buying and selling transactions using a sales memorandum. This allows duplicate data to occur due to repeated customer and supplier data writing. Based on the above problems, the author wants to propose a multiuser-based inventory system design to be taken into consideration in helping to speed up the process of recording purchase and sales transactions and can provide the information needed at the Semarang Mini Iron Store in the form of inventory reports, sales level reports and daily income reports in the form of an application Inventory system in Semarang Mini Iron Shop using Visual Basic 6.0 and MySql database. Making this application is expected to be one of the efforts that can be done to overcome the problems that often occur so as to increase the effectiveness of work which will certainly affect the quality of service to customers.